Dysregulation of the Lateral Habenula in Major Depressive Disorder - Browne, Caroline A.; Hammack, Robert; Lucki, Irwin (Frontiers in Synaptic Neuroscience, 2018)
Clinical and preclinical evidence implicates hyperexcitability of the lateral habenula (LHb) in the development of psychiatric disorders including major depressive disorder (MDD). This discrete epithalamic nucleus acts as a relay hub linking forebrain limbic structures with midbrain aminergic centers. Central to reward processing, learning and goal directed behavior, the LHb has emerged as a critical regulator of the behaviors that are impaired in depression. Stress induced activation of the LHb produces depressive and anxiety-like behaviors, anhedonia and aversion in preclinical studies. Moreover, deep brain stimulation of the LHb in humans has been shown to alleviate chronic unremitting depression in treatment resistant depression. The diverse neurochemical processes arising in the LHb that underscore the emergence and treatment of MDD are considered in this review, including recent optogenetic studies that probe the anatomical connections of the LHb.